1 3/8 is left because 12 - 10 5/8 is 1 3/8
Answer:
g(3a – 6) = a - 4
Step-by-step explanation:
g(x) = 1/3x - 2
g(3a – 6) = 1/3(3a – 6) - 2
= a - 2 - 2
= a - 4
Answer:
Option d. the initial amount of money placed in the savings account
Step-by-step explanation:
we have
![f(x)=3,005(1+0.03)^{x}](https://tex.z-dn.net/?f=f%28x%29%3D3%2C005%281%2B0.03%29%5E%7Bx%7D)
This is a exponential function of the form
![f(x)=a(1+r)^{x}](https://tex.z-dn.net/?f=f%28x%29%3Da%281%2Br%29%5E%7Bx%7D)
where
a is the initial value
r is the growth rate
(1+r) is the base
x is the number of years
f(x) is the amount of money in a savings account
In this problem we have
a=$3,005
r=0.03=3%
(1+r)=1.03
therefore
3,005 represent the initial value ( the amount of money for the value of x equal to zero)
Step-by-step explanation:
sorry I don't now but when I now I will tell you ok but mybe it 12×12×12
Answer:
The functions are inverses; f(g(x)) = x ⇒ answer D
⇒ answer D
Step-by-step explanation:
* <em>Lets explain how to find the inverse of a function</em>
- Let f(x) = y
- Exchange x and y
- Solve to find the new y
- The new y = ![f^{-1}(x)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29)
* <em>Lets use these steps to solve the problems</em>
∵ ![f(x)=\sqrt{x-3}](https://tex.z-dn.net/?f=f%28x%29%3D%5Csqrt%7Bx-3%7D)
∵ f(x) = y
∴ ![y=\sqrt{x-3}](https://tex.z-dn.net/?f=y%3D%5Csqrt%7Bx-3%7D)
- Exchange x and y
∴ ![x=\sqrt{y-3}](https://tex.z-dn.net/?f=x%3D%5Csqrt%7By-3%7D)
- Square the two sides
∴ x² = y - 3
- Add 3 to both sides
∴ x² + 3 = y
- Change y by ![f^{-1}(x)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29)
∴ ![f^{-1}(x)=x^{2}+3](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3Dx%5E%7B2%7D%2B3)
∵ g(x) = x² + 3
∴ ![f^{-1}(x)=g(x)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3Dg%28x%29)
∴ <u><em>The functions are inverses to each other</em></u>
* <em>Now lets find f(g(x))</em>
- To find f(g(x)) substitute x in f(x) by g(x)
∵ ![f(x)=\sqrt{x-3}](https://tex.z-dn.net/?f=f%28x%29%3D%5Csqrt%7Bx-3%7D)
∵ g(x) = x² + 3
∴ ![f(g(x))=\sqrt{(x^{2}+3)-3}=\sqrt{x^{2}+3-3}=\sqrt{x^{2}}=x](https://tex.z-dn.net/?f=f%28g%28x%29%29%3D%5Csqrt%7B%28x%5E%7B2%7D%2B3%29-3%7D%3D%5Csqrt%7Bx%5E%7B2%7D%2B3-3%7D%3D%5Csqrt%7Bx%5E%7B2%7D%7D%3Dx)
∴ <u><em>f(g(x)) = x</em></u>
∴ The functions are inverses; f(g(x)) = x
* <em>Lets find the inverse of h(x)</em>
∵ h(x) = 3x² - 1 where x ≥ 0
- Let h(x) = y
∴ y = 3x² - 1
- Exchange x and y
∴ x = 3y² - 1
- Add 1 to both sides
∴ x + 1 = 3y²
- Divide both sides by 3
∴ ![\frac{x + 1}{3}=y^{2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%20%2B%201%7D%7B3%7D%3Dy%5E%7B2%7D)
- Take √ for both sides
∴ ± ![\sqrt{\frac{x+1}{3}}=y](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7Bx%2B1%7D%7B3%7D%7D%3Dy)
∵ x ≥ 0
∴ We will chose the positive value of the square root
∴ ![\sqrt{\frac{x+1}{3}}=y](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7Bx%2B1%7D%7B3%7D%7D%3Dy)
- replace y by ![h^{-1}(x)](https://tex.z-dn.net/?f=h%5E%7B-1%7D%28x%29)
∴ ![h^{-1}(x)=\sqrt{\frac{x+1}{3}}](https://tex.z-dn.net/?f=h%5E%7B-1%7D%28x%29%3D%5Csqrt%7B%5Cfrac%7Bx%2B1%7D%7B3%7D%7D)